Effect of longitudinal deformation on wave propagation in truss core sandwich panel. (January 2021) - Liang, Sun; Yougang, Xiao
The longitudinal deformation has been ignored by most previous study on vibroacoustic behaviours of truss core sandwich panels. This paper investigates its effect by developing two theoretical models. One, named as full model, considers both flexural and longitudinal deformation of face sheets while the other, named as flexural model, incorporates only flexural deformation. By comparing free characteristic waves obtained from two models, one find that flexural model ignore two waves, that is, a compressive wave and a global flexural one. The ignored waves cause vibration in transverse direction even at high frequencies, and thus result in vibration peaks under forced vibration. Therefore the flexural model would underestimate the vibration response, and the longitudinal deformation of face sheets cannot be ignored during dynamic analysis of the sandwich panels.